Advancing self‐healing soy protein hydrogel with dynamic Schiff base and metal‐ligand bonds for diabetic chronic wound recovery - Tian Lan; Yabo Dong; Jiajia Shi; Xing Wang; Zejian Xu; Yan Zhang; Lianzhou Jiang; Weibiao Zhou; Xiaonan Sui (Aggregate, 2024)
Abstract To address the unique challenges of diabetic wound healing, wound dressings, particularly multifunctional hydrogels have garnered considerable interest. For the first time, a novel environmentally friendly soy protein‐based hydrogel is developed to accelerate the healing of diabetic chronic wounds. Specifically, this hydrogel framework is in direct formation through the dynamic Schiff base between oxidized guar gum and epigallocatechin‐3‐gallate (EGCG)‐modified soy protein isolate. Meantime, the addition of Ag+ enhances the cross‐linking of the hydrogel network by forming metal‐ligand bonds with the catechol groups in EGCG. Interestingly, the stretchability (up to 380%), swelling, and rheology properties of the hydrogel can be controlled by fine‐tuning the density of metal‐ligand bonds, endowing them with a high potential for precise matching. Additionally, various dynamic bonds endow hydrogel with excellent self‐healing ability, adhesiveness, and injectability. This hydrogel also exhibits good antibacterial properties, biocompatibility, and cell migration capabilities. Both in vivo and in vitro experiments demonstrated the outstanding anti‐inflammatory capacity of the hydrogel and its ability to modulate macrophage polarization. Consequently, the hydrogel has proven effective in promoting wound healing in a diabetic full‐thickness wound model through enhanced angiogenesis and collagen deposition. This eco‐friendly plant protein hydrogel offers a sustainable solution for wound care and environmental protection.